EFFECT OF SEASON ON PHYSIOLOGICAL PARAMETERS OF THREE BREEDS OF CATTLE RAISED IN SUDAN SAVANNA ZONE (FUDMA JOURNAL OF SCIENCES, 2021)
This study was conducted to test the effect of season and breed on thermoregulatory parameters of three Nigerian indigenous breeds of cattle raised in Sudan Savanna Zone. A total number of nine (9) cattle aged between 4-5 years were used for this study. Data were taken for sixteen weeks across two seasons; Cold and Hot Season from three indigenous breed of cattle. Rectal temperature was recorded using digital thermometer, pulse rate was determined using stethoscope and respiratory rate was determined by counting of the respiratory movements of flank area. Data of ambient temperature and relative humidity were recorded on daily basis and temperature humidity index was calculated. All data obtained were subjected to analysis of variance using SAS software. Seasons significantly (P < 0.05) affect all the thermoregulatory parameters of with hot seasons having the highest values. Breed influenced (p
Keywords: thermoregulatory parameters, Red Bororo, SokotoGudali, season